CAESAREAN SECTION RATE AND INDICATIONS AT SULAIMANI MATERNITY TEACHING HOSPITAL WITH REVIEW OF LITERATURE - Mustafa, Chnur Younis; Mahmood, Maryam Bakir (Journal of Sulaimani Medical College, 2019)
Background Caesarean section (C-section) is a frequent obstetric intervention for saving the lives of women and their newborns from childbirth-related complications. Objectives The aim was to know the rate and indications of C-section in the Kurdistan-Iraq. Patients and Methods Retrospectively-collected data from a single large public institution, Maternity Teaching Hospital, in Kurdistan-Iraq was analysed. All women giving birth in 2016 with a known birth outcome were included. Those who underwent C-section were identified, and indications were recorded. Data analysed using descriptive statistics. A review of literature looking at rate and indication of C-section was performed. Results Five thousand and eight hundred sixty (38.4%) of mothers who gave birth from 15235, required C-section. The total number of born-baby was 18573; of them, 259 babies died (1.4%)—(192, 74.1%) following Normal Vaginal Delivery and (67, 25.9%) during C-section. 27% of mothers were primigravida, and the rest were multigravida. Emergency C-section was performed in 4106 (70.1%). The history of ≥2 C-sections was the main indication for C-section (25.7%) followed by breech presentation (13.9%), fetal distress (12.5%), failure of progress (11.9%), failure of induction (11.8%), antepartum haemorrhage (8.3%) and pre-eclampsia (6.8%). There were three maternal mortalities (0.01%), but no maternal mortality following C-section Conclusion With the continued war against the Islamic state and economic turmoil, health service in Kurdistan suffered most, but with the goodwill of healthcare professionals, our institution showed comparable results to places elsewhere. Monitoring of clinical indications of C-section is needed to ensure the rational use of the procedure.
Keywords: Caesarean Section; C-Section; Normal Vaginal Delivery; Incidence; Kurdistan